Development of Test Instruments Based on Problem Solving at The High School Level - Ditya Lufita; Rita Juliani (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
Â Research on the development of problem solving-based test instruments at the high school level was carried out aimed at measuring studentâ€™s problem solving abilities according to the problem solving aspect of Polya and knowing the feasibility of test instruments in terms of validity, reliability, discriminatory power, and level of difficulty. This type of research is research and development with the ADDIE model namely Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at Al Ulum Terpadu Islamic High School Medan with the research subject being XII MIA, totaling 15 students for small groups and 35 students for large groups. The results of the expert validation stated that the 15 questions developed were in the very feasible category. The results of the small group of 15 questions obtained 10 valid questions with a reliability value of 0.89 in the high category, the difficulty level of the items was 0.46-0.95 and the discriminating power of the items was 0.03-0.71. The results of the large group obtained 10 questions in the valid category and a reliability value of 0.93 in the high reliability category, the difficulty level of the items was 0.29-0.54 and the different power of the items was 0.13-0.55.